The Native American Occupation of Alcatraz Island: Radio and Rhetoric - Megan Engle (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2019)
In order to draw attention to the numerous social and economic plights facing indigenous populations, a group of Native American protesters occupied Alcatraz Island from November 1969 to June 1971. Throughout the nineteen months of occupation, protesters received much attention from the media. While in theory this coverage may have been beneficial, the media presented the story in a largely negative and inaccurate light. Upon review of the literature, it becomes evident that the media used racist and poor journalistic practices to diminish the protest. To counter this biased view, the occupiers released their own news via radio. A comparative analysis of selected Radio Free Alcatraz broadcasts and selected releases from the mainstream media sources of the time demonstrates a dichotomy in the presentation of the situation and reveals a series of discriminatory tendencies in the journalistic portrayal of Native Americans. Understanding this divide and these tendencies in the presentation of minorities may allow for a greater understanding of contemporary race and media relations.
Keywords: Native American; Occupation; Alcatraz; Rhetoric